Corporate Governance, Ownership Structure And Corporate Diversification: Evidence From The Malaysian Listed Companies - Che Ahmad, Ayoib; Ishak , Zuaini; Abd Manaf, Nor Aziah (Asian Academy of Management (AAM), 2003)
Previous research has contributed much to our understanding of the relationship between corporate diversification strategy and corporate governance quality. The majority of published works has been on sophisticated and mature markets in first world nations. This paper extends previous knowledge by examining this relationship in a developing country. Malaysia is a developing country that provides a rich setting for corporate governance research. The structure of the business environment and the availability of published data make it an interesting research site